Can and should the research–therapy distinction be maintained? Reflections in the light of innovative last-resort treatment. (April 2019) - Helgesson, Gert
It has been debated for quite some time among bioethicists and others whether or not the distinction between therapy and research in healthcare can and should be maintained. This paper tries to clarify what the disagreement is about, and argues that the distinction can be maintained in most, if not all, situations. However, even if it can be maintained, it does not necessarily follow that it should. It is argued here that there are good reasons to maintain the distinction both for the sake of protecting research interests and the sake of patient safety. In addition, recognizing the distinction provides a barrier against unreasonable prioritization between patients. However, there may be situations, such as innovative last-resort treatment, in which regulatory requirements from both therapy and research should be considered.